1991
DOI: 10.1002/1520-6629(199104)19:2<178::aid-jcop2290190209>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Radio psychology talk show hosts: Assessment of counseling style

Abstract: Radio psychology talk show hosts' responses were analyzed using the 14‐category Hill Counselor Verbal Response Category System (HCVRCS) and then compared with the verbal behaviors of other professional and non‐ professional helpers, including Carl Rogers, Fritz Perls, Albert Ellis, family practice lawyers, and mutual‐help group leaders. Radio hosts tended to be active and directive in their verbal behaviors, offering primarily advice and information, and only infrequently reflecting, restating, or self‐disclos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Cummings (1989) found that counselors in training used more information with clients who presented intrapersonal problems compared to more reflection with clients who presented interpersonal problems, which lends support to our findings (Hill, 1989) that therapists respond differently depending on client type and problems. Levy, Emerson, and Brief (1991) compared the response modes of radio talk show hosts with those of expert therapists (Rogers, Perls, and Ellis in the study by Hill, Thames, & Rardin, 1979), mental health professionals, family practice lawyers, and nonprofessional mutual-help group leaders (the latter three groups studied by Toro [1986]). Radio hosts' verbal behavior was most similar to that of Ellis and Perls in that all were active and directive.…”
Section: Research Findingsmentioning
confidence: 99%
“…Cummings (1989) found that counselors in training used more information with clients who presented intrapersonal problems compared to more reflection with clients who presented interpersonal problems, which lends support to our findings (Hill, 1989) that therapists respond differently depending on client type and problems. Levy, Emerson, and Brief (1991) compared the response modes of radio talk show hosts with those of expert therapists (Rogers, Perls, and Ellis in the study by Hill, Thames, & Rardin, 1979), mental health professionals, family practice lawyers, and nonprofessional mutual-help group leaders (the latter three groups studied by Toro [1986]). Radio hosts' verbal behavior was most similar to that of Ellis and Perls in that all were active and directive.…”
Section: Research Findingsmentioning
confidence: 99%
“…Using data in Table 1, we formed ranks for the verbal response mode use for each column (representing a single helper or type of helper). We then compared rank orders across columns, using the same analytic procedures as Levy et al (1991) used to compare types of helpers. We did Spearman rank-order correlations between the career counselors and each of the other types of helpers, using a .01 level of significance because of the number of correlations.…”
Section: Resultsmentioning
confidence: 99%
“…Again using the HCVRCS, Levy, Emerson, and Brief (1991) compared radio psychology talk show hosts with other helpers. They analyzed 12 caller-host conversations involving four doctoral level psychologists who hosted call-in programs taken from Levy (1989) and compared the results with the data on Carl Rogers, Fritz Perls, and Albert Ellis taken from the Hill et al (1979) study and with mental health professionals, group leaders, and lawyers from the Toro (1986) study.…”
mentioning
confidence: 99%
“…Psychologists used the newspapers, radio, and television to disseminate psychological information and so educate the public about the mental health aspects of stress reactions, particularly those of children; to give some guidelines for handling the more frequent difficulties with children; and to teach, particularly via television, the use of educational games for both relaxation and fun and working through the stresses of the war as a family together. The community/mass-oriented programs placed emphasis on educational and preventive goals (Levy, Emerson, & Brief, 1991;Schwebel, 1982) and thereby represented another major outreach by school psychologists into the public domain at crucial points during the Gulf crisis.…”
Section: Mass Communicationmentioning
confidence: 99%
“…In addition, radio call-in psychology talk programs were offered. Levy et al (1991) suggested that such programs may be of benefit because of "nonspecific factors" related to the caller's expectations, the host's prestige and status, and the atmosphere of respect, acceptance, warmth, and empathy between caller and host. The very act of calling, it was suggested, may be helpful, irrespective of the actual conversation.…”
Section: Mass Communicationmentioning
confidence: 99%